React.JS : the complete course for beginners. (Manning Publications, 2022)
React JS has taken center stage in easing the creation of dynamic user interfaces for websites and apps. Because JavaScript is one of the most widely used languages for websites and apps, it's no wonder that many people are working on libraries and frameworks to help it grow. And one of the most popular is React, which allows you to create unique HTML components and create sophisticated apps in a short amount of time. However, these frameworks and libraries are not always simple to understand. And that's where this course comes in: it breaks down challenging ideas, making them easy to comprehend even for newcomers to the development field. The course is enjoyable, engaging, and interactive. It takes a hands-on approach to React JS, and includes fun projects, such as building a calculator app, to put your new skills into practice. Lessons are are backed up with essential learning tools, such as quizzes and assignments, to reinforce what you learn and help it stick.